Evaluation of Novel Approaches to Software Engineering : 9th International Conference, ENASE 2014, Lisbon, Portugal, April 28-30, 2014. Revised Selected Papers - Maciaszek, Leszek A.; Filipe, Joaquim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 9th International Conference on Evaluation of Novel Approaches to Software Engineering, ENASE 2014, held in Lisbon, Portugal, in April 2014. The 11 full papers presented were carefully reviewed and selected from 58 submissions. The papers reflect a growing effort to increase the dissemination of new results among researchers and professionals related to evaluation of novel approaches to software engineering. By comparing novel approaches with established traditional practices and by evaluating them against software quality criteria, the ENASE conferences advance knowledge and research in software engineering, identify most hopeful trends, and propose new directions for consideration by researchers and practitioners involved in large-scale software development and integration.
Reducing the Level of Complexity of Working with Model Transformations -- Learning from the Current Status of Agile Adoption -- A Case Study Investigation of a Lightweight, Systematic Elicitation Approach for Enterprise Architecture Requirements -- Using a Domain Specific Language for Lightweight Model-Driven Development -- A Study of the Relationship between Class Testability and Runtime Properties -- Online Testing: A Passive Approach for Protocols -- Experiences of Use of a Multi-Domain Tool for Collaborative Software Engineering Tasks -- Taking Seriously Software Projects Inception through Games. Natural Language Generation Approach for Automated Generation of Test Cases from Logical Specification of Requirements -- Visualization, Simulation and Validation for Cyber-Virtual Systems -- Mobile Application Estimate the Design Phase.
Keywords: Software engineering; Information Systems; Information technology; Software Engineering; Management of Computing and Information Systems; Information Systems Applications (incl. Internet).; IT in Business